(3Shb GdaGVd aj efGbH GdbGVi GdaGVds - (3ceGd GdOjf YeQ Hf CMeO Hf gHI Gddg Hf CHj LQGOI GdYbjdj GdMdHj, CHj MaU , GdeYQha HGHf GdYOje,J (B660 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CXgQ ai Thb GdGOH hLg GdOdGdI hHYO aEfi hbaJ Ydi cKjQ ef JhGQjN GdeJbOejf hWGdYJ Ydi LedI eG JVefJg ef JQGLe GdhRQGA s
(3BNQgG (B:s
(3BNQg CHjGJ TYQjI bhdI HPcQfj GdYgO GdbOje dCfgG MOjKI YgO ef Cgjd jhOfi s
(3gh eLehYI ai GTYGQ HYV GdYdeGA GdCaGVd ai fgGjJg NWhW eNJdaIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B40s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs